DAMPAK SOSIAL PENAMBANGAN EMAS TANPA IZIN (PETI) DI DESA SUNGAI SORIK KECAMATAN KUANTAN HILIR SEBERANG KABUPATEN KUANTAN SINGINGI - Trisnia Anjami; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Essay submitted to fulfill requirement sociology deagree. The study was conducted in kabupaten kuantan singing whit the aim of obtaining the impormation of the social impact of illegal gold mining. Several problem in this study are (1) who the perpetrators of gold mining without permission in the village sungai sorik (2) what are the social impact of illegal gold mining in the village sungai sorik (3) whether there is a relationship of social mobility of livelihood to social mobility. The title of this study “The Social Impact Of Illegal Gold Mining In The Village Sungai Sorik Kecamatan Kuanta Hilir Seberang Kabupaten Kuantan Singingi”. This research aimed to find out who the perpetrator gpld mining without permission in sungai sorik. To know the social impact that result gold mining without permission in sungai sorik. To know the relationship of livelihood change to social mobility. This reseach is a quantitative research because is natre is shapecase. After doing this research, the result of the study note the social impact of illegal gold mining in sungai sorik is a miner, social impact, and livelihood change relationship of social mobility. Perpretators of this social impact of wokers which has an individual or grup get a fropit. Or a lot of mining product and to achieve its ob actives. Existence of the prepetators, social impact, and livelihood change relationship to social mobility so as o tringger the occorence social impact of illegal gold mining in sungai sorik.Keywords: Social Impact, Anauthorized Gold Miners